Hyaluronic acid‐sperm selection significantly improves the clinical outcome of couples with previous ICSI cycles failure. (8th February 2022) - Scaruffi, Paola; Bovis, Francesca; Casciano, Ida; Maccarini, Elena; De Leo, Caterina; Gazzo, Irene; Massarotti, Claudia; Sozzi, Fausta; Stigliani, Sara; Anserini, Paola
Abstract: Background: Beneficial effects of hyaluronic acid (HA)‐based selection of spermatozoa for intracytoplasmic sperm injection (ICSI) are still controversial, and further studies are needed to categorize patients that might benefit from such a method. Objective: We investigated whether HA sperm selection improved ICSI outcome of couples with previous ICSI cycle failure. Materials and methods: In this retrospective study, we prospectively collected data of (i) Group 1: 96 couples who performed one failed ICSI cycle ("1st procedure, " n  = 96) followed by another ICSI cycle ("2nd procedure, " n  = 101); ii) Group 2: 87 couples who performed one failed ICSI cycle ( n  = 87) followed by an HA‐ICSI cycle ( n  = 104). Differences between procedures and groups were measured by paired and independent statistical tests, respectively. A generalized linear mixed model analyzed the effect of procedure on the outcomes and the interaction between procedures and groups. Results: Injection of HA‐bound sperm significantly improved cleavage rate with respect to standard ICSI ( p  = 0.026). No evolutive pregnancies were obtained in the 1st ICSI attempts. The 2nd ICSI cycles resulted in successfully seven pregnancies. In HA‐ICSI cycles, the better quality of embryos with respect to ICSI ( p  = 0.034) increased the choice of day 5 embryo transfer ( p  = 0.030), which resulted in successfully 28 pregnancies. No differences were observed in clinical outcomes of the two ICSI procedures in Group 1, while pregnancy and implantation rates were significantly higher in HA‐ICSI with respect to ICSI cycles ( p  = 0.001, p  < 0.0001, respectively). No negative perinatal outcomes were recorded. Discussion: In couples where previous 1st ICSI failed, selection of HA‐bound spermatozoa significantly improved clinical outcomes with respect to further standard ICSI. Conclusion: This study identified couples with previous ICSI cycles failure as a category of infertile patients that really may benefit from HA sperm selection before ICSI.